(untitled) (Revista Argentina de Musicología, 2022)
The appearance of talking films opened the door for many artists to immortalize musical works that were never recorded. This was replicated years later by the experience of Argentine rock music. Whether by writing a film’s soundtrack, playing a part in an archive-based documentary, as a musical act within a work of fiction, or an advertisement jingle, Argentine rock musicians left their vocal and instrumental mark in the recording of audiovisual productions. The music that Charly García wrote for the film Pubis Angelical (1982) was edited into an album that shares the film’s name, and it is also the first album from his solo discography. In other instances, less fortunate recordings were thrown away, lost or forgotten. More recently, film material that had not seen the light of day were found, restored and recirculated. We are specifically referring to the discarded shots from the Almendra documentary (1969) and the shooting of Manal en el Parque Garay (1979). In this paper, we intend to make a reading of these records allow us to rethink some of the notions that are tied to the rock history in Argentina.